There is no dog - Rosoff, Meg (G. P. Putnam's Sons, 2012)
When the beautiful Lucy prays to fall in love, God, an irresponsible youth named Bob, chooses to answer her prayer personally, to the dismay of this assistant, Mr. B who must try to clean up the resulting catastrophes.